Analisis desain kurikulum Bahasa Arab: Komponen dan Relevansi dengan Kebutuhan pembelajaran Abad ke-21 - Fatimah Azzahra Putri; Sulthon, Athian; Ubaid Ridho (Rayah Al-Islam, 2026)
This study aims to analyze the design of the Arabic language curriculum by examining its components and relevance to 21st-century learning needs. The background of this research is based on the increasing demand for education that is responsive and adaptive to global challenges, particularly in the digital era and the Industrial Revolution 4.0. The research focuses on aligning Arabic language learning with essential skills of the 21st century, including critical thinking, creativity, communication, collaboration, digital literacy, and cross-cultural competence. A qualitative descriptive method was employed by reviewing relevant literature, research findings, and policy documents on Arabic language education and curriculum innovation. The results indicate that the Arabic curriculum needs to integrate technology, project-based learning, and culturally contextual materials to enhance communication skills and real-world application among students. Furthermore, periodic teacher training is essential to master modern teaching methods and utilize supportive technologies effectively. Evaluation systems should also be more comprehensive by incorporating both theoretical knowledge and practical skills. This study concludes that the design of the Arabic language curriculum should not only serve as a guide for teaching but also as a strategic instrument to equip students with global competencies aligned with the demands of the 21st century.